Human Resource Management Practices and Strategy for Retention in Private Schools in Bayelsa State - Onukwu , James N.; Okafor, Ikechukwu Maduka (International Journal of Educational Management, 2021)
The sustainability and growth of the school system is dependent on available human potentials. This study investigated the practice of human resource management and retention among private schools in Bayelsa State, Nigeria. The study adopted descriptive research design. The population of the study was all the teachers in private schools in Bayelsa State. Two research questions and one hypothesis guided the study. A total of 120 teachers were randomly selected for the study and only 100 responded to the questionnaire (83.5%). A questionnaire titled:“ Human Resource Practice in Private Schools Questionnaire (HRMPPSQ) was used to collect data for the study. The questionnaire was validated and Cronbach Alpha was used to test the reliability and the co-efficient value of 0.92 was obtained. The result revealed low level human resource management and retention practice. It further showed that there is no significant difference in the responses of the teachers. The study thenrecommended among others that there should be trainings, workshops and skills development on best human resource management practice in private schools.